Pengaturan Hak Mendapatkan Informasi Publik Berdasarkan Peraturan Daerah Propinsi Jambi Nomor 3 Tahun 2014 - Herma Yanti; Supeno Supeno; Nazifah Nazifah (Universitas Batanghari Jambi, 2023)
Jambi Province Regional Regulation Number 3 of 2014 concerning Public Information Services for the Implementation of Regional Government is a follow-up to the provisions of Law Number 14 of 2014 concerning Public Information Disclosure (UU KIP). However, the provisions regarding the arrangements for submitting requests for information dispute resolution to the Information Commission based on Regional Regulation Number 3 of 2014. This research is normative legal research with a comparative legal approach and statutory approach. From the results of the research it is known that for the provision of public information it turns out that the requirements and time limits specified in the Perda actually exceed the provisions specified in UU KIP. Meanwhile for the submission of an application for settlement of information disputes by the Petitioner to the Information Commission, it turns out that the Perda does not contain clear and complete arrangements as stipulated in the UU KIP.